Simulação atomística de sistema em nanoescala - Fabris, Guilherme da Silva Lopes [UNESP] (2015)
In this work we investigate mechanical and electronic properties of graphene based materials. Using classical molecular dynamics with the reactive potential ReaxFF, we studied mechanical properties of hexagonal BN nanoribbons, where BN atoms are randomly replaced by C atoms; we considered concentrations of 0% C (pure hBN) up to 100% C (pristine graphene). Our results show that for BNC nanoribbons, the substitution of BN pairs by C atoms causes a reduction on mechanical stregth until concentrations close to 40% to 60%. On the other hand, higher concentrations result in a fast enhancement on the mechanical stregth, reaching values close to that found for graphene. We studied also electronic properties of nanotubes constructed using either the Porous Graphene (PG) or BPC structure. Tight Binding Density Functional (DFTB) theory was applied to calculate the band structure and density of states of these systems considering various different chiralities. Both the PG and the BPC nanotubes presented gaps around the values presented by their original sheets, namely 3:3eV and 0:7eV respectively; another interesting fact is the effect of an increase on the nanotube's diameter over the gap, which trends were different between the two classes of nanotubes considered